Textbook Evaluation on “Bright An English Course” for Seventh Grade Students - Vini Eviolin; Fitrawati Fitrawati (Journal of English Language Teaching, 2023)
Textbook is one of the main learning materials teachers use to help the teaching and learning process run well. This study's goal was to assess a textbooks in general attributes and the learning-teaching content criteria. Descriptive qualitative research was used in this research.. The source of data of this research is an English textbook entitled “Bright an English Course” For Seventh Grade” for Grade 7 Students, published by Erlangga and was analyzed using the evaluation format proposed by Mukundan et al. (2011). The finding of this research showed that the English textbook “Bright an English Course” for seventh-grade junior high school students had fulfilled the criteria for a good textbook, scoring 92,75% or was categorized as excellent on the aspect of the general attributes. On the learning-teaching content aspect, this textbook has not fully fulfilled the criteria by achieving the sum point of 79.7% or is still categorized as good. Overall, the quality of this textbook was categorized as excellent, with the total was 86,22%. By using the findings from the previous analysis, this textbook can be characterized as a reliable reference in teaching and learning process.